2009
DOI: 10.1080/15321810903187922
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Passive Immunization with IgY Antibodies to a 58-kDaH. pyloriAntigen on Severe Gastritis in BALB/c Mouse Model

Abstract: Consecutive triple doses of 1 x 10(8) CFU/mL of a pathogenic H. pylori strain isolated from stomach of Egyptian patients with severe gastritis were used to establish infection in BALB/c mice model. White Leghorn hens were immunized with H. pylori whole cell lysate (HpLysate) antigen and with a highly reactive 58-kDa H. pylori (Hp58) antigen. Two months later, IgY antibodies (IgY-HpLysate & IgY-Hp58) were purified from egg yolk and its efficacy was evaluated in the adopted model. Microbiological culture and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Such anti-bacterial and anti-inflammatory effects of IgY seem to be higher than the efficacy of IgY-Hp that exhibited 50-60% anti-inflammatory activity at 180 mg/kg in a gerbil model [35]. Furthermore, the efficacy of IgY was superior to the H. pylori -elimination ratio (70%) of IgY-Hp58 specific for 58-kDa H. pylori (Hp) antigen [38]. On the other hand, it was reported that urease-specific IgY significantly attenuated gastric inflammation of gerbils fed at a concentration of 25 mg/g diet [39].…”
Section: Discussionmentioning
confidence: 99%
“…Such anti-bacterial and anti-inflammatory effects of IgY seem to be higher than the efficacy of IgY-Hp that exhibited 50-60% anti-inflammatory activity at 180 mg/kg in a gerbil model [35]. Furthermore, the efficacy of IgY was superior to the H. pylori -elimination ratio (70%) of IgY-Hp58 specific for 58-kDa H. pylori (Hp) antigen [38]. On the other hand, it was reported that urease-specific IgY significantly attenuated gastric inflammation of gerbils fed at a concentration of 25 mg/g diet [39].…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58] Our group previously developed a reliable murine model for H. pylori infection. 59 In addition, we developed IgY antibodies in chickens that target a pathogenic H. pylori strain and used these antibodies to treat infected mice. Passively immunized mice had a significantly lower degree of infection and gastritis than unimmunized animals.…”
Section: Immunoglobulin Y Antibodiesmentioning
confidence: 99%
“…Passively immunized mice had a significantly lower degree of infection and gastritis than unimmunized animals. 59 Oral administration of anti-H. pylori IgY can be used a complementary therapy combined with routine antibiotic therapy. 60…”
Section: Immunoglobulin Y Antibodiesmentioning
confidence: 99%
“…This approach mimics naïve protection in humans and has been shown to be effective in the prevention and treatment of a variety of pathogens, such as Rotavirus, Clostridium difficile , and Campylobacter jejuni [ 17 21 ]. Many animal studies have shown that bovine antibody-containing milk against H. pylori reduces bacterial load, thus preventing and even eradicating H. pylori infection [ 22 25 ]. However, the available clinical studies of bovine antibodies in milk have not shown H. pylori eradication [ 26 29 ].…”
Section: Introductionmentioning
confidence: 99%